No general stability conditions for marine ice-sheet grounding lines in the presence of feedbacks - Olga V. Sergienko (Nature Communications, 2022)
Using theoretical, numerical and data analyses, this study finds that there are no general stability conditions for marine ice sheets if feedbacks caused by interactions of ice sheets with atmosphere, ocean and lithosphere are taken into account.